Staycation as Complementary Tourism in Bali - Sari Suyasa, Ni Luh Christine Prawitha; Susanto, Putu Chris; Satyananda, Agus (Akademi Komunitas MAPINDO, 2023)
Staycation is a strategy used by accommodation providers in Bali to increase room occupancy rates. Staycation travelers, are local people, also take tour packages to spend time with family, self-healing for those who are not married, and even for those who work remotely. This study aims to analyze staycation offers during the low season or when the Covid-19 Pandemic hit Indonesia, especially the island of Bali which relies on tourism to support the movement of its economic sector. The method used in this research is descriptive qualitative by conducting in-depth interviews with 5 (five) staycation tourism connoisseurs who are doing staycation at least 3 (three) times during the Covid-19 Pandemic. The results of this study state that it is proven that staycation is a complementary tourism during the Covid-19 Pandemic or in the Low Season, because local people / tourists who have contributes high numbers to the room occupancy rate in Bali. The relatively cheaper price that can be paid by local tourists compared to domestic or foreign tourists, but can still pay for the operational costs of accommodation service providers which have a positive impact on the tourism sector which is able to boost the economic sector on the island of Bali in particular. This complementary tourism is expected to reduce dependence on foreign tourists and can provide new appreciation for local/domestic tourists and can be relied upon as a promotional strategy not only during the Covid-19 Pandemic, but beyond. Keywords: Accommodation Providers, Complementary Tourism, Staycation, Staycation Connoisseurs